2016
DOI: 10.2134/cftm2015.0202
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Yield Response and Plant Structure Following Increased Nitrogen Rates and Plant Growth Regulator Applications in Kentucky

Abstract: To increase wheat (Triticum aestivum L.) yield in Kentucky, many producers are increasing nitrogen (N) rates to 160 or 180 lb N/ acre and applying a plant growth regulator (PGR) to reduce plant height and lodging. Replicated field trials were established in three environments (Princeton 2014, Princeton 2015, Lexington 2015 to determine whether increased nitrogen rates and/or PGR applications increase yield or alter the structure of the wheat plant. Five N rates (0, 50, 100, 150, 200 lb N/acre), three cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 1 publication
8
24
1
Order By: Relevance
“…Increased wheat grain yield following PGR application was also reported by Matysiak (2006) and Penckowski et al (2009). In contrast, Rajala and Peltonen‐Sainio (2002), Wiersma et al (2011), and Knott et al (2016) did not observe increased grain yield following PGR applications. In the present study, PGR increased yield even when lodging was minimal or nonexistent perhaps due to physiological changes within the plant as increased tiller density following PGR application has been reported in multiple wheat cultivars and cool‐season turfgrasses (Ervin and Koski, 2001; Hafner, 2001; Rajala and Peltonen‐Sainio, 2001).…”
Section: Wheat Grain Yield Response To Plant Growth Regulator and Nitcontrasting
confidence: 56%
See 4 more Smart Citations
“…Increased wheat grain yield following PGR application was also reported by Matysiak (2006) and Penckowski et al (2009). In contrast, Rajala and Peltonen‐Sainio (2002), Wiersma et al (2011), and Knott et al (2016) did not observe increased grain yield following PGR applications. In the present study, PGR increased yield even when lodging was minimal or nonexistent perhaps due to physiological changes within the plant as increased tiller density following PGR application has been reported in multiple wheat cultivars and cool‐season turfgrasses (Ervin and Koski, 2001; Hafner, 2001; Rajala and Peltonen‐Sainio, 2001).…”
Section: Wheat Grain Yield Response To Plant Growth Regulator and Nitcontrasting
confidence: 56%
“…Data on other wheat physiological responses to PGR are limited. Knott et al (2016) reported increased spikelets head −1 following PGR application. Little information regarding the effect of PGR rate or application timing in wheat is available.…”
Section: Using Plant Growth Regulators To Improve Small Grains Producmentioning
confidence: 98%
See 3 more Smart Citations